Implementation of the Numbered Heads Together Type Cooperative Learning Model - Nasrulloh, Muhammad Farid; Amalia, Rheina Futih; Umardiyah, Fitri; Wafa, Muhammad Aliyul (SCHOOLAR: Social and Literature Study in Education, 2024)
This research aims to determine the improvement in student learning outcomes in the application of the Numbered Heads Together type cooperative learning model in the Al-Qur'an Hadith subject in class XI MA Unggulan KH. A. Wahab Hasbullah. The research method used is a quantitative method with a pre-experimental design with one group pre-test – post-test. The sampling technique used simple random sampling for class XI- Mathematics and Natural Science students, totaling 50 students. Data collection was carried out using tests. Data analysis uses the Paired Samples Test. The research results show that there is a significant increase in student learning outcomes after implementing the Numbered Heads Together model. The students' average pretest score was 53.20, while the average posttest score increased to 77.20. Statistical analysis using the t-test shows a significance value (Sig.) of 0.001, which indicates that the difference between the pre-test and post-test scores is very statistically significant. This research concludes that the Numbered Heads Together type cooperative learning model is effective in improving student learning outcomes in the Al-Qur'an Hadith subject.